Biomechanical analysis of transverse patella fracture fixation techniques - S, Deleep (Nanyang Technological University, 2023)
Patella fractures form 1% of all fractures in adults, of which the transverse fracture is the most common type. The patella is a crucial part of the extensor mechanism of the knee, playing an important role in daily movement and regular activities like bending down and walking.